1986
DOI: 10.1084/jem.164.6.2061
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a pore-forming protein of human peripheral blood natural killer cells.

Abstract: We show here that human peripheral blood NK cells contain a pore-forming protein (PFP) with an Mr of 70,000-72,000 that assembles structural lesions (with an average internal diameter of 150-170 A) and forms functional channels. The PFP was isolated by affinity chromatography from human NK cells, using a specific anti-C9 antiserum as the immunoadsorbent. The NK cells were isolated from PBL by positive or negative selection by indirect rosetting using a panel of monoclonal antibodies directed against different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
34
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 61 publications
1
34
0
Order By: Relevance
“…However, the identity of the crossreactive proteins and the extent of the immunological crossreactivity were not determined in those studies. Recent results (8)(9)(10) have shown that C9 and PFP/perforin display structural, immunological, and functional similarities . Both species have been shown to undergo polymerization to form circular lesions .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the identity of the crossreactive proteins and the extent of the immunological crossreactivity were not determined in those studies. Recent results (8)(9)(10) have shown that C9 and PFP/perforin display structural, immunological, and functional similarities . Both species have been shown to undergo polymerization to form circular lesions .…”
Section: Discussionmentioning
confidence: 99%
“…Structural, functional and immunological similarities between the ninth component of complement (C9) and the lymphocyte pore-forming protein (PFP, perforin) have recently been described (8)(9)(10) . PFP is shown here to be immunologically related to all other components of the membrane attack complex …”
Section: Discussionmentioning
confidence: 99%
“…PFP is postulated to intercalate the target cell membrane and compromise its osmotic stability; however, the function of SEs in the cytotoxic process is less clear. Intriguing parallels have been drawn between this mechanism and the complement cascade, including the close similarities between the immunological and physicochemical properties ofPFP and C9, the ninth component ofcomplement (7,(10)(11)(12) .…”
mentioning
confidence: 99%
“…PFP is postulated to intercalate the target cell membrane and compromise its osmotic stability; however, the function of SEs in the cytotoxic process is less clear. Intriguing parallels have been drawn between this mechanism and the complement cascade, including the close similarities between the immunological and physicochemical properties ofPFP and C9, the ninth component ofcomplement (7,(10)(11)(12) .Many ofthe granule polypeptides have been purified to homogeneity, and cDNA clones encoding PFP (13-16) and several of the SEs (17-25) have recently been characterized. To further analyze the role of PFP in the cytolytic process and the basis for its immunological and evolutionary relationship to C9, we have investigated the This work was supported in part by U. S.…”
mentioning
confidence: 99%
“…They showed that, instead of oxygen metabolites, killer cells released a pore-forming protein by granulemediated exocytosis. Young isolated from killer cell granules this "perforin" (260,285,291), as well as two serine esterases (294). Young characterized the lesions that were created by perforin deposition in targets as large ion-carrying pores and visualized the pores by electron microscopy (292).…”
mentioning
confidence: 99%